(untitled) (Advancements in Homeopathic Research, 2024)
Background: Diabetes mellitus has been known to mankind since antiquity as a “Honeyed Urine” disease in ancient literature, “Madhu-Meh” in Hindi, and “Sugar disease” in layman’s language. This research evaluates the therapeutic potential of a homoeopathic Mother Tincture derived from Tinospora cordifolia for treating diabetic nephropathy. The study began with phytochemical screening and standardization of the plant extract. Subsequently, its antioxidant and anti-diabetic properties will be evaluated in vivo. Finally, the research will induce and assess the Homoeopathic Mother Tincture’s ability to mitigate the complications associated with diabetic nephropathy. Method: This study investigates the potential of a mother tincture in preventing diabetic nephropathy in rats. Rats were divided into groups of 6, and diabetes was induced by injecting Streptozotocin (STZ) followed by nicotinamide to prevent severe hypoglycemia. Only rats with a fasting blood glucose level ≥250 mg/dl after 72 hours were included. Different doses of the mother tincture (100, 200, and 400 mg/kg) were selected based on reported oral acute toxicity studies, and the development of diabetic nephropathy was assessed by measuring elevated serum urea, uric acid, creatinine, and BUN levels. Result: Tinospora cordifolia has been shown to significantly reduce blood glucose levels, food and water intake, creatinine levels, uric acid levels, and triglycerides. Conclusion: This study observed significant reductions in Sugar Levels using Mother Tincture of Tinospora cordifolia for diabetic nephropathy. These encouraging findings warrant further investigation due to limitations. Therefore, we recommend larger, longer-duration studies to confirm efficacy and safety for managing diabetic nephropathy.